Development of mWellcare: an mHealth intervention for integrated management of hypertension and diabetes in low-resource settings. Issue 1 (1st January 2018) - Jindal, Devraj; Gupta, Priti; Jha, Dilip; Ajay, Vamadevan S.; Goenka, Shifalika; Jacob, Pramod; Mehrotra, Kriti; Perel, Pablo; Nyong, Jonathan; Roy, Ambuj; Tandon, Nikhil; Prabhakaran, Dorairaj; et al.
ABSTRACT: Background : Cardiovascular diseases and diabetes are among the leading causes of premature adult deaths in India. Innovative approaches such as clinical decision support (CDS) software could play a major role in improving the quality of hypertension/diabetes care in primary care settings. Objective : To describe the steps and processes in the development of mWellcare, a complex intervention based on mobile health (mHealth) technology. Methods : The Medical Research Council framework was used to develop mWellcare in four steps: (1) identify gaps in usual care through literature review and health facility assessments; (2) identify the components of the intervention through discussions and consultations with experts; (3) develop intervention (clinical algorithms and mHealth system); and (4) evaluate acceptability and feasibility through pilot testing in five community health centers. Results : Lack of evidence-based, integrated, and systematic management of chronic conditions were major gaps identified. Experts in information technology, clinical fields, and public health professionals identified intervention components to address these gaps. Thereafter, clinical algorithm contextualized to primary care settings were prepared and the mWellcare intervention was developed. During the 2-month pilot, 631 patients diagnosed with hypertension and/or diabetes were registered, with a follow-up rate of 36.2%. The major barrier was resistance to follow mWellcare recommended patient workflow, and to overcome it, we emphasized onsite training and orientation program to cover all health care team member in each CHC. Conclusion : A pilot-tested mWellcare intervention is an mHealth system with important components, i.e. integrated management of chronic conditions, evidence-based CDS, longitudinal health data and automated short-messaging service to reinforce compliance to drug intake and follow-up visit, which will be used by nurses at primary health care settings in India. The effectiveness and cost-effectiveness of the intervention will be tested through a cluster randomized trial (trial registration number NCT02480062).